Sleep disruption considerations for Paralympic athletes competing at Tokyo 2020 - Roberts, I. E.; Murphy, C. J.; Goosey-Tolfrey, V. L. (The Journal of Sports Medicine and Physical Fitness, 2021)
The role of sleep is now recognized as an important component for success in athletic performance, and sleep is proposed to be one of the most effective recovery strategies available. Insufficient sleep is commonly reported among athletes while several factors have been put forward to explain why elite athletes might experience poor sleep. However, Paralympic athletes may be predisposed to a greater risk of poor sleep due to the associated complexities of some impairment types. In fact, clinical research has previously shown that individuals with disabilities have a higher prevalence of sleep disturbances when compared to their able-bodied counterparts. However, research and evidence-based practices regarding the sleep of elite Paralympic athletes are limited. Firstly, this narrative review aims to identify challenges associated with the Paralympic games to obtain optimal sleep. Secondly, identify the specific risk factors to sleep associated with particular impairment groups within the Paralympic population, and lastly to propose potential sleep-enhancing strategies that might be of relevance for Paralympic athletes. From this review, initial observations have identified that Paralympic athletes may have a heightened risk of sleep-related problems, and importantly highlighted the current lack of understanding within this population group. Furthermore, this review identified where further research is warranted to better understand how specific impairments impact sleep and, consequently, athletic performance. Additionally, this review highlighted that the forthcoming Tokyo games may offer a unique challenge for athletes trying to obtain optimal sleep, due to the anticipated thermal demands and the consequent irregular scheduling of events.